2008
DOI: 10.4278/ajhp.22.3.155
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Tailored Aerobic Exercise Intervention for Low-Income Latinas

Abstract: Participants in the exercise group reported more vigorous exercise (p < .001) and walking (p = .005) at post-test than controls. Aerobic dance and unsupervised activity resulted in a five-fold greater increase in relative VO2max compared with controls (p < .001). Although exercise and fitness decreased at follow-up, vigorous exercise (p = .001) and relative VO2max (p < .001) remained higher in the exercise group, suggesting maintenance at 1 year. CONDUSION:. Culturally tailored aerobic dance can increase vigor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(130 citation statements)
references
References 12 publications
5
125
0
Order By: Relevance
“…Eight studies [29,38,48,[54][55][56][57][58] reported on Hispanic participants as all or part (50% or greater) of their study population of interest. Two studies purposively recruited a combination of Hispanic and African American participants [54,56].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies [29,38,48,[54][55][56][57][58] reported on Hispanic participants as all or part (50% or greater) of their study population of interest. Two studies purposively recruited a combination of Hispanic and African American participants [54,56].…”
Section: Resultsmentioning
confidence: 99%
“…Common administrative retention strategies were to obtain multiple alternate contact numbers for participants [37,53,64], make multiple (10-20) contacts with participants during the study period [31,38,39,45,53,54,57], and maintain detailed databases and tracking registries for participants [29,37,59]. Providing financial or other incentives, transportation, or childcare were also commonly mentioned [29, 37-40, 42, 43, 45, 46, 48-50, 54-59, 63, 64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…¶ In fact, 1 study achieved retention rates as high as 91% at 1 year. 5 Thus, attrition did not appear problematic in this literature compared to similar reviews conducted among African Americans. 45 …”
Section: Recruitment and Retentionmentioning
confidence: 85%
“…5,6,34 Providing incentives also proved effective at increasing attendance at group sessions and assessments. For example, Hovell et al 5 awarded raffle tickets for attending classes and gave out prizes during each class.…”
Section: Recruitment and Retentionmentioning
confidence: 95%